Study of fungi associated with some selected vegetables of Dhaka City (Bangladesh Journal of Scientific Research, 2012)
DOI: http://dx.doi.org/10.3329/bjsr.v24i2.10776 Bangladesh J. Sci. Res. 24(2):181-184, 2011 (December)